PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SLIDE PADA MATA PELAJARAN KIMIA SMA KELAS X MATERI STRUKTUR ATOM - Zulfadli Zulfadli; Kana Puspita; Sulastri Sulastri (Chimica Didactica Acta, 2022)
The research entitled "Development of Google Slide-Based Interactive Learning Media on Chemistry Subjects in Class X High School Materials on Atomic Structure", has been carried out using Research and Development (RD) research types and the ADDIE model. The purpose of this study is to develop a google slide learning media that is proven to be suitable for use. The google slide-based learning media on atomic structure material was tested for feasibility by expert validators (media and materials) and students of MAS Darussyari'ah, Banda Aceh city. The instrument in this study was a media feasibility questionnaire sheet and student response sheets. The results of data analysis showed that the google slide media was very feasible to use with the percentage of media feasibility validation results of 93%. Students responses to the media showed a positive response with a percentage of 86.37% which was categorized as very good. Based on the data obtained, it can be concluded that the Google Slide media is very suitable to be used as a learning medium and received positive responses from students.